Peran Evaluasi dalam Meningkatkan Proses dan Hasil Pembelajaran Menulis pada Siswa Kelas VII SMP 1 Tarakan - Riyanti, Asih; Kasmawati, Kasmawati; Asrimayani, Asrimayani; Natali, Deswita; Tiara, Tiara (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study aims to determine the role of evaluation in improving the process and results of writing learning in grade VII students of Tarakan 1 Middle School. Evaluation in writing learning not only functions as a measuring tool for learning outcomes, but also as a means to improve the effectiveness of the learning process itself. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews and documentation. The results of the study indicate that the implementation of appropriate evaluation, both formative and summative, is able to provide constructive feedback to students and teachers. This feedback plays an important role in improving learning strategies and improving students' writing skills, especially in terms of structure, vocabulary, and writing. Thus, this evaluation has a contribution in creating a more effective writing learning process and more optimal learning outcomes.